2020
DOI: 10.2196/17632
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Improve Apathy in Residential Aged Care: Mixed Methods Study

Abstract: Background Apathy is a common symptom in neurological disorders, including dementia, and is associated with a faster rate of cognitive decline, reduced quality of life, and high caregiver burden. There is a lack of effective pharmacological treatments for apathy, and nonpharmacological interventions are a preferred first-line approach to treatment. Virtual reality (VR) using head-mounted displays (HMDs) is being successfully used in exposure- and distraction-based therapies; however, there is limit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 93 publications
3
75
0
3
Order By: Relevance
“…Other studies using VR and looking at apathy have also been single session studies, therefore, not examining changes in apathy (Benoit et al, 2015;Manera et al, 2016). A recent feasibility study (Saredakis, Keage, Corlis, & Loetscher, 2020), found that participants with varying levels of cognitive decline ranging from minimal to moderate impairment could tolerate the use of VR with HMDs in agreeance with previous research (Huygelier, Schraepen, van Ee, Vanden Abeele, & Gillebert, 2019). The VR reminiscence experience in this study was specifically tailored for each participant.…”
Section: Introductionsupporting
confidence: 79%
“…Other studies using VR and looking at apathy have also been single session studies, therefore, not examining changes in apathy (Benoit et al, 2015;Manera et al, 2016). A recent feasibility study (Saredakis, Keage, Corlis, & Loetscher, 2020), found that participants with varying levels of cognitive decline ranging from minimal to moderate impairment could tolerate the use of VR with HMDs in agreeance with previous research (Huygelier, Schraepen, van Ee, Vanden Abeele, & Gillebert, 2019). The VR reminiscence experience in this study was specifically tailored for each participant.…”
Section: Introductionsupporting
confidence: 79%
“… 27 Other studies using VR and looking at apathy have also been single-session studies, therefore, not examining changes in apathy. 28 29 A recent feasibility study, 30 found that participants with varying levels of cognitive decline ranging from minimal-to-moderate impairment could tolerate the use of VR with HMDs in agreeance with previous research. 31 The VR reminiscence experience in this study was specifically tailored for each participant.…”
Section: Introductionsupporting
confidence: 79%
“…18% (n = 15) offered interventions focusing on activities for social engagement, entertainment or comfort ( 41‐52,54,55 ; Van der 53 ). The interventions aimed at increasing older people's QoL through encouraging communication and offering positive experiences and thereby relieving and managing psychogeriatric symptoms such as behavioral and psychological symptoms in dementia (BPSD) or depression.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions used robotic pets, 41,43,45,48‐50 social robots, 44 tablets for apps or videos, 46,47,54 videoconferences (Van der 53 ), virtual reality technology, 42,51,52 and light therapy 55 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation